(untitled) (Estudios Sociales, 2023)
In Argentina, the myths of the European origin of its population and the extinction of the original peoples have been in force for 140 years. They have had explanatory force to deny not only rights to native peoples but also to publicly affirm their very extinction. Since the end of the last military dictatorship (1976-1983) and the return of democracy, the existence and rights of native peoples have been recognized. At the same time, there was a strong criticism of the entire historiographical account that had supported these myths. However, in the present, the debate about history continues. In the current context of political confrontation between different models, we find new discourses that articulate old explanations based on those myths. After the tendency to criticize the traditional discourse, new revisionist and denialist proposals have been established, anchored in the current political context. These reuse and redefine the stereotypes of foreign and Chilean indigenous peoples, the myth of innate violence and the illegitimacy of the claim of rights by native peoples. These discursive constructions accompany a process of increasing violence towards the organizations and demands of the original peoples in Patagonia, where the Mapuche people are identified as an internal enemy. In this paper we propose to address this context taking into account the scientific production on the historical process of indigenous subjugation and incorporation into the state-nation-territory matrix in Argentina, focusing especially on the case of Patagonia and the Mapuche people.